Discretionary Fiscal Policies over the Cycle: New Evidence based on the ESCB Disaggregated Approach - Luca Agnello; Jacopo Cimadomo (European Central Bank (ECB), 2009)
This paper explores how discretionary fiscal policies on the revenue side of the government budget have reacted to economic fluctuations in European Union countries. For this purpose, it uses data on legislated revenue changes and structural indicators provided twice per year by National Central Banks of European Union countries in the ESCB framework for analysing fiscal policy. The analysis is based on the estimation of fiscal policy rules linking these measures of legislated fiscal policy changes to the output gap and other control variables. Then, baseline results are compared with regression estimates where variations of cyclically-adjusted indicators are used as proxy for discretionary fiscal policies, as conventionally proposed in the empirical literature on fiscal policy. Results suggest that, overall, legislated changes in taxes and social security contributions have responded in a strongly pro-cyclical way to the business cycle, while commonly-used cyclical-adjustment methods point to a-cyclicality.
Keywords: E62; E65; H20; 330; cyclical sensitivity; Discretionary fiscal policies; ESCB disaggregated framework; government revenues; legislation changes; narrative approach; Finanzpolitik; Regelbindung versus Diskretion; Öffentliche Einnahmen; Konjunktur; Aggregation; EU-Staaten